Korunets’ I.V. Contrastive Typology of the English and Ukrainian Language - Швачко, С. (Мовознавство, 2007)
Рецензія на книгу: Korunets’ I.V. Contrastive Typology of the English and Ukrainian Language. Вінниця : Нова Книга, 2004.— 460 с.